Consensus recommendations on fasting during Ramadan for patients with kidney disease: review of available evidence and a call for action (RaK Initiative) - Yousef Boobes; Bachar Afandi; Fatima AlKindi; Ahmad Tarakji; Saeed M. Al Ghamdi; Mona Alrukhaimi; Mohamed Hassanein; Ali AlSahow; Riyad Said; Jafar Alsaid; Abdulkareem O. Alsuwaida; Ali A. K. Al Obaidli; et al. (BMC Nephrology, 2024)
Abstract Ramadan fasting (RF) involves abstaining from food and drink during daylight hours; it is obligatory for all healthy Muslims from the age of puberty. Although sick individuals are exempt from fasting, many will fast anyway. This article explores the impact of RF on individuals with kidney diseases through a comprehensive review of existing literature and consensus recommendations. This study was conducted by a multidisciplinary panel of experts. The recommendations aim to provide a structured approach to assess and manage fasting during Ramadan for patients with kidney diseases, empowering both healthcare providers and patients to make informed decisions while considering their unique circumstances.